2010
DOI: 10.1080/01411920903165603
|View full text |Cite
|
Sign up to set email alerts
|

A synthesis of studies searching for school factors: Implications for theory and research

Abstract: This paper reports the results of a meta‐analysis in which the dynamic model of educational effectiveness is used as a framework to search for school factors associated with student achievement. The methods and results of a synthesis of 67 studies are presented. Findings reveal that effective schools are able to develop policies and take actions in order to improve their teaching practice and learning environment. Factors excluded from the dynamic model were found to be only weakly associated with outcomes. Im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
105
0
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 125 publications
(118 citation statements)
references
References 23 publications
1
105
0
12
Order By: Relevance
“…Kyriakides & Christoforou, 2011) The first two elements are important components of measuring classroom climate, as classroom environment research has shown (Cazden, 1986;Den Brok, Brekelmans, & Wubbels, 2004;Fraser, 1991). The other three elements refer to the attempt of teachers to create a business-like and supportive environment for learning, especially since research on teacher effectiveness reveals that the classroom environment should not only be business-like but needs to be supportive for students (Walberg, 1986).…”
Section: Classroom Climatementioning
confidence: 99%
“…Kyriakides & Christoforou, 2011) The first two elements are important components of measuring classroom climate, as classroom environment research has shown (Cazden, 1986;Den Brok, Brekelmans, & Wubbels, 2004;Fraser, 1991). The other three elements refer to the attempt of teachers to create a business-like and supportive environment for learning, especially since research on teacher effectiveness reveals that the classroom environment should not only be business-like but needs to be supportive for students (Walberg, 1986).…”
Section: Classroom Climatementioning
confidence: 99%
“…Specifically, the proposed approach to school improvement has its own theoretical framework which refers to factors of educational effectiveness that need to be considered in introducing a change at school level. By making use of the dynamic model of educational effectiveness (Creemers & Kyriakides, 2008), this approach draws attention to the importance of improving school policy for teaching and the school learning environment since these two overarching factors were found to be associated with student achievement gains (Kyriakides, Creemers, Antoniou, & Demetriou, 2010;Hattie, 2009;Scheerens, Seidel, Witziers, Hendriks, & Doornekamp, 2005).…”
Section: Establishing a Dynamic Approach To School Improvement: Assummentioning
confidence: 98%
“…This test includes all structural path between the latent variables in the model and the overall fit of the hypothesized structural model.If the overall fit is unacceptable, then the model has to be modified based on the theory. [40] suggests categories fit in evaluating a model that has been built. Information about the kind of fit this category is summarized in the Table 1 as below: This chapter discusses the methodology of the study.Hypotheses was tested by using the quantitative method.…”
Section: Methodsmentioning
confidence: 99%